Operational scenario of first high luminosity LHC run. Issue 1 (1st January 2023) - Tomás, R; Arduini, G; Baudrenghien, P; Brüning, O; Bruce, R; Buffat, X; Calaga, R; Cerutti, F; Maria, R De; Dilly, J; Efthymiopoulos, I; Giovannozzi, M; et al.
Abstract: A new scenario for the first operational run of the High Luminoisty LHC (HL–LHC) era (Run 4) has recently been developed to accommodate a period of performance ramp-up to achieve an annual integrated luminosity close to the nominal HL–LHC design target. The operational scenario in terms of beam parameters and machine settings, as well as the different phases to reach optimal performance, are described here along with the impact of potential delays to key hardware components.